2019
DOI: 10.1094/mpmi-03-19-0059-r
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Role of Amino Acids from Sesbania rostrata Seed Exudates in the Chemotaxis Response of Azorhizobium caulinodans ORS571

Abstract: Azorhizobium caulinodans ORS571 can induce nodule formation on the roots and the stems of its host legume, Sesbania rostrata. Plant exudates are essential in the dialogue between microbes and their host plant and, in particular, amino acids can play an important role in the chemotactic response of bacteria. Histidine, arginine, and aspartate, which are the three most abundant amino acids present in S. rostrata seed exudates, behave as chemoattractants toward A. caulinodans. A position-specific-iterated BLAST a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Azorhizobium caulinodans ORS571, a symbiont of the host Sesbania rostrata , can fix atmospheric nitrogen in free-living and symbiotic states. As reported for other rhizobia symbiotic associations (Caetano-Anolles et al, 1988; Merritt et al, 2007; Miller et al, 2007; Scharf et al, 2016), the establishment of the A. caulinodans-S. rostrata association involves chemotaxis toward plants roots, colonization of the root surface, infection, and the initiation of nodule organogenesis (Jiang et al, 2016; Liu et al, 2017, 2019a,b; Liu W. et al, 2018; Liu X. et al, 2018). In particular, two chemoreceptors, IcpB and TlpA1, were shown to be involved in the chemotactic response of A. caulinodans to some organic acids, such as succinate, citrate, tartrate, and malate (Jiang et al, 2016; Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Azorhizobium caulinodans ORS571, a symbiont of the host Sesbania rostrata , can fix atmospheric nitrogen in free-living and symbiotic states. As reported for other rhizobia symbiotic associations (Caetano-Anolles et al, 1988; Merritt et al, 2007; Miller et al, 2007; Scharf et al, 2016), the establishment of the A. caulinodans-S. rostrata association involves chemotaxis toward plants roots, colonization of the root surface, infection, and the initiation of nodule organogenesis (Jiang et al, 2016; Liu et al, 2017, 2019a,b; Liu W. et al, 2018; Liu X. et al, 2018). In particular, two chemoreceptors, IcpB and TlpA1, were shown to be involved in the chemotactic response of A. caulinodans to some organic acids, such as succinate, citrate, tartrate, and malate (Jiang et al, 2016; Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 64%
“…Recently, we have found that aspartate, histidine, and arginine in seed exudates have indirect effects promoting the chemotactic response to succinate (Liu et al, 2019a). Therefore, we investigated whether oxalate also has an indirect effect on response to other organic acids using the soft agar plate assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two chemoreceptor mutants, Δ azc_0821 and Δ azc_0660 , were also employed to investigate the role of chemoreceptors on the calcium-mediated biofilm formation. The two chemoreceptors AZC_0821 (also termed as TlpH) and AZC_0660 (also termed as TlpA1) have broad-range ligands including organic acids and amino acids ( Liu et al, 2017b ; Liu et al, 2019b,c ). At 6 or 12 h, they both showed a significant decrease of biofilm biomass compared to wild type ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%